O significado do estoicismo na 'Crítica da razão prática' de Kant - Neilson Jose da Silva (2013)
This master's research aims to investigate the meaning of stoicism in the Kritik der praktischen Vernunft (KpV) of Kant. However, this study does not intend to establish comparison between Kant and the Stoics. Rather, this research aims to discuss how Kant understands the Stoic ethic in the text of the second critique. For this study it was necessary at first distinguish the concepts: conditioned (das Bedingte) and unconditioned (das Unbedingte) to understand the possible uses of reason: theoretical use and practical use. Secondly, after admitting the possibility of practical use of reason, it was necessary to distinguish between the concepts of moral law (Das moralische Gesetz) and highest good (das höchste Gut) in order to subsidize the examination of notions of morality and happiness. The examination of the relation between morality and happiness, in the composition of the highest Good, led this study to its third step. At this stage, we carried out the analysis of Kant's position on Stoic ethic. For this, it was necessary to identify the passages of the second critique in which Kant refers to the Stoics. Thus, the study presented the several objections of Kant in relation to Stoic ethic. Kant's objections in relation to the items in the Stoic notion of virtue: such as suicide (der Selbstmord), highest good (das höchste Gut), arrogance (die Arroganz), heroism (der Heroism), moral fanaticism (moralische Schuwärmerei) were taken as basis to prove the thesis of overcoming of stoicism in the field of practical reason.